Comparative Effect of Cinnamon Powder and Red Ginger Powder for Menstrual Pain Primary Dysmenorrhea in Adolescent - Diah Evawanna Anuhgera; Riris Sitorus; Debi Dinha Octora (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Menstrual pain is a problem with interferes by women in every menstrual cycle. This can interfere with the activities of women such as dizziness, nausea, stomach cramps, and productivity of women. Several non-pharmacologic treatment can help reduce menstrual pain such as giving cinnamon and red ginger. The purpose of this study was to compare the effectiveness of cinnamon powder and red ginger to decrease menstruation in adolescents with primary dysmenorrhea. This type of research is a quasi-experimental type of time series design. The sample in this study were all first semester female students in the Nursing Study Program at the Lubuk Pakam Medistra Health Institute who experienced primary dysmenorrhea as many as 28 people. The sampling technique used is simple random sampling. In this study there were two groups, namely the control group with the administration of ginger powder while the intervention group with the administration of cinnamon powder. The process was given an intervention for 3 days and the use of the research instrument to measure menstrual pain was the Numeric Rating Scale (NRS). Data analysis used independent t-test and Repeated Measured Anova test. The results showed that there was a difference in mean pain before and before cinnamon powder at 24 hours of intervention after (p<0.001) while red ginger drink powder showed no significant difference in mean pain before and before the intervention in the first 24 hours of intervention (p = 0.112). However, at 48 hours and 72 hours of intervention for the two groups, there was a significant difference in the decrease in mean menstrual pain in primary dysmenorrhea (p<0.001). Cinnamon drink powder is more effective than red ginger drink powder in reducing primary dysmenorrhea menstrual pain. Cinnamon and red ginger can be used as an effective non-pharmacological treatment intervention and obtained as a treatment for primary removal. Midwives can educate and apply the intervention of cinnamon and red ginger drinks to adolescents with primary dysmenorrhea.